Melancolia em Repertório Selvagem, de Olga Savary, e Metade cara, metade máscara, de Eliane Potiguara - SENA, Mayara Haydée Lima (Universidade Federal do Pará, 2025)
This study focuses on the images of melancholy that emerge in the context of coloniality in two of its Brazilian expressions: indigenous and Amazonian sadness. The so-called peripheral sadnesses are represented by the books Metade cara, metade máscara (2004), by Eliane Potiguara, and Repertório Selvagem (1998), by Olga Savary, which make up the corpus of this research. The aim is to identify allegorized melancholy as a fundamental theme in the poetics of Eliane Potiguara's Metade cara, metade máscara and Olga Savary's Repertório selvagem. Furthermore, the specific objectives are to discuss some relationships between the coloniality of knowledge and the silencing of peripheral, non-canonical, Brazilian and Amazonian sadness; to identify indigenous melancholy, metonymized in Eliane Potiguara's work; and to investigate images of melancholy in the shadow of the Amazonian forest in Olga Savary's book. The work recalls canonical authors of studies on melancholy, such as Sigmund Freud (2013), Julia Kristeva (1989), Giorgio Agamben (2007), Susan Sontag (2022), Jean Starobinski (2016), Susana Kampff Lages (2007), Luiz Costa Lima (2017), Maria Rita Kehl (2015), among others; dialogues with the decolonial perspective of thinkers such as Aníbal Quijano (2005), Enrique Dussel (2005), Walter Mignolo (2017), María Lugones (2014); with scholars of Amazonian issues, such as Neide Gondim (1994), Ana Pizarro (2012),Carlos Walter Porto Gonçalves (2023), Eidorfe Moreira (1958) and João de Jesus Paes Loureiro (2001); and with indigenous thinkers such as Graça Graúna (2013), Trudruá Dorrico (2017), Davi Kopenawa (2015), Jaider Esbell (2020), Ely Makuxi (2018), Ailton Krenak (2022), Olívio Jekupé (2019), Daniel Munduruku (2012), among others. Thus, there is a need for a more specific debate on the Brazilian experience of malaise, which is crossed by coloniality and therefore differs from Eurocentric understandings of sadness and its literary representations. In this sense, based on the interpretative path of the poems, it is recognized that the indigenous literature of Eliane Potiguara and the omnipresence of the Amazon rainforest in the work of Olga Savary, place other characters and territories in the repertoire of melancholy studies in contemporary times, outside the hegemonic melancholy of large European cities. The authors' poetic contributions are fundamental to making peripheral sadness visible, creating a counter-narrative that challenges the coloniality of knowledge about melancholy. In Savary's poetics, the Amazons, in terms of their phytogeographic concept (MOREIRA, 1958), are inscribed under the sign of loss; as well as in Eliane Potiguara's poetic testimony, it is revealed that coloniality cannot be thought of without the reign of sadness.